The role of dinoprostone for labor induction in postterm and high-risk term pregnancies - I.F. Urunsak; U.K. Gulec; E. Eser; M. Sucu; C. Akcabay; S. Buyukkurt (IMR Press, 2020)
Purpose: To determine the effect of controlled release vaginal dinoprostone (CRVD) in post-term and high-risk term pregnancies on successful ripening, the length of active labour, the total time for delivery, route of delivery, and maternal-neonatal outcomes. Methods: We performed a retrospective study on women undergoing cervical ripening with CRVD. A total of 94 post-term pregnancies (group 1) were compared with 138 high-risk pregnancies requiring labour induction due to maternal and/or fetal indications at term (group 2). The primary outcome of the study was vaginal delivery within 24 hours. Length of active labour, the total time for delivery, route of delivery and maternal and neonatal outcomes were evaluated as secondary outcomes. Results: Vaginal delivery rates were 73.4% (69/94) and 81.9% (113/138) in groups 1 and 2, respectively (p = 0.123). The mean delivery lengths were 16.6 ± 9.5 and 16 ± 8.9 hours in groups 1 and 2, respectively (p = 0.259). Both groups were also similar regarding the length of active labour (9.3 ± 6.7 and 9.6 ± 6.8 hours; p = 0.717). Cesarean section rates were 23.4% and 13% in groups 1 and 2, respectively (p = 0.04). There were no differences in maternal and neonatal outcomes between the groups. Conclusion: Our study showed that dinoprostone is effective for labour induction, particularly in high-risk term pregnancies.